1990
DOI: 10.1159/000226830
|View full text |Cite
|
Sign up to set email alerts
|

Biological Effects of Adrenal Androgens on MCF-7 and BT-20 Human Breast Cancer Cells

Abstract: The MCF-7 human breast cancer cell line responds to 5-androstene-3β,17β-diol, to dehydro-epiandrosterone and to its 3β-sulfate stimulation in vitro by increased proliferation. 5-Androstene-3β,17β-diol has the strongest mitogenic effect. Dehydroepiandrosterone has a more potent action on cell proliferation than its 3β-sulfate. These adrenal androgens do not stimulate proliferation of the estrogen receptors negative for the BT-20 cell line. In our conditions, we have failed to demonstrate MCF-7 estradiol formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…Nonetheless, some ER-positive BC cell lines, such as MCF-7 and MDA-MB-453, are growth stimulated by androgens and inhibited by anti-androgens (Birrell et al 1995, Cochrane et al 2014. Other data show a proliferative response of ER-positive BC cell lines to adrenal androgens (Poulin & Labrie 1986, Najid & Habrioux 1990, Boccuzzi et al 1992, Maggiolini et al 1999, Billich et al 2000.…”
Section: Figurementioning
confidence: 98%
“…Nonetheless, some ER-positive BC cell lines, such as MCF-7 and MDA-MB-453, are growth stimulated by androgens and inhibited by anti-androgens (Birrell et al 1995, Cochrane et al 2014. Other data show a proliferative response of ER-positive BC cell lines to adrenal androgens (Poulin & Labrie 1986, Najid & Habrioux 1990, Boccuzzi et al 1992, Maggiolini et al 1999, Billich et al 2000.…”
Section: Figurementioning
confidence: 98%
“…Epidemiological and experimental studies suggest that they might affect the growth of human breast tumours (Bulbrook et al, 1971;Wang et al, 1975;Segaloff et al, 1980;Zumoff et al, 1981;Helzlsouer et al, 1992). In vitro studies showed that they may exert a dual and opposite effect on the growth of breast cancer cells (Adams et al, 1981;Poulin & Labrie, 1986;Najid & Habrioux, 1990;Boccuzzi et al, 1992a). ADIOL is able to stimulate the in vitro growth of oestrogen-dependent breast cancer cell lines in steroid-free medium when added at the concentrations found in the plasma of post-menopausal women (Nahoul et al, 1985).…”
mentioning
confidence: 99%
“…Neither G6PD activity nor cell growth is affected by DHEA in SR-cells; conversely, the growth of the SR+ cells is stimulated by DHEA, but G6PD activity is not affected. The stimulatory action of DHEA on cell growth depends on its metabolization to ADIOL, a compound which binds to ERs (Adams et al, 1981;Najid and Habrioux, 1990;Boccuzzi et al, 1992b, Pizzini et al, 1992. This result does not support the theory that DHEA plays a role in the growth of breast cancer through G6PD modulation.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, the use of a hormoneresponsive cell line obscures the mechanism of the action on cell growth because of the overlap of hormonal and non-hormonal effects. More precisely, the proliferative effects of DHEA that are due to ER binding of its metabolite ADIOL (Adams et al, 1981;Najid and Habrioux, 1990) may mask an antiproliferative action because of G6PD inhibition. In view of this, we evaluated DHEA DHEA and G6PD in breast cancer cells 591 action on G6PD activity and growth in both SR-negative and SRpositive cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation